Photoswitching of Azobenzene-Based Reverse Micelles above and at Subzero Temperatures As Studied by NMR and Molecular Dynamics Simulations - Filipová, Lenka (Langmuir : the ACS journal of surfaces and colloids, 2017)
We designed and studied the structure, dynamics, and photochemistry of photoswitchable reverse micelles (RMs) composed of azobenzene-containing ammonium amphiphile 1 and water in chloroform at room and subzero temperatures by NMR spectroscopy and molecular dynamics simulations. The NMR and diffusion coefficient analyses showed that micelles containing either the E or Z configuration of 1 are stable at room temperature. Depending on the water-to-surfactant molar ratio, the size of the RMs remains unchanged or is slightly reduced because of the partial loss of water from the micellar cores upon extensive E → Z or Z → E photoisomerization of the azobenzene group in 1. Upon freezing at 253 or 233 K, E-1 RMs partially precipitate from the solution but are redissolved upon warming whereas Z-1 RMs remain fully dissolved at all temperatures. Light-induced isomerization of 1 at low temperatures does not lead to the disintegration of RMs remaining in the solution; however, its scope is influenced by a precipitation process. To obtain a deeper molecular view of RMs, their structure was characterized by MD simulations. It is shown that RMs allow for amphiphile isomerization without causing any immediate significant structural changes in the micelles